LITERARY LEARNING FOR TEENAGER INMATES IN INSTITUTE FOR CHILDREN SPECIAL REHABILITATION - Anwar Efendi; Rachma Nurjanah (Jurnal Cakrawala Pendidikan, 2019)
Children who are afflicted with problems of the law must remain entitled to obtain services, guidance, education, protection, and fulfillment of their rights. This is directed to help children to prepare for their future life which is better and more dignified. The study is aimed at describing the nurture of children offenders, the running, and the benefits of literacy learning for inmates who receive rehabilitation treatment in the Institute for Children Special Rehabilitation (ICSR) of Class II B of Yogyakarta Province, Indonesia. The study is descriptive qualitative research involving 23 inmates and one instructor. Data are obtained from observations, interviews, and documents. Data analyses are done in three phases; namely selection, presentation, and conclusion. The findings are as follows. First, the rehabilitation phases in the ICSR are orientation, personality nurture, advanced nurture, and integration. Orientation and nurture phases are conducted in the ICSR, while integration is done outside the institute. Second, the literary learning activities are run informally taking the inmate conditions into consideration. Instructional materials consist of poetry writing, poetry musicalization, and basic exercises in drama staging. Third, literary learning gives benefits in character education, the betterment of social adaptation, and media for catharsis.